Zasady stosowania zrównoważonej karty wyników w warunkach funkcjonowania polskich miast - Nieplowicz, Maria (The rules of using the balanced scorecard in Polish cities, 2006)
The article shows the main rules of using the Balanced Scorecard taking into consideration polish cities specificity as well as the advantages of using the Balanced Scorecard.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 278-283